L’islam tropical face à la mort - Michelangelo Giampaoli (Revue des Mondes Musulmans et de la Méditerranée)
This article aims to present a study of the Islamic Cemetery of Guarulhos (São Paulo), in order to understand both the history of a sacred space of one of the most important Muslim communities in Brazil and its forms of (self)representation. Connected by the common religious faith, Brazilian Muslims are, however, individuals with very different personal and family histories of migration. Far from their birthplaces in Syria, Lebanon, Iran, many of them ended up being buried in Brazil, next to Brazilians converted to Islam. The analysis of the processes that lead those people to the choice of this specific place, to the creation of monuments, inscriptions and epitaphs and the development of ritual practices - through which this community renew the relationship with its own origin, starting from the relationship built with death - allows today to reconstruct the history and the memories of a specific Islamic community, as well as its progressive interaction with the complex and multicultural Brazilian context.